Motivational profile analysis about groups of athletes and their impact on the sporting satisfaction - Manzano Sánchez, D.; Valero Valenzuela, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2013)
The purpose of this study was to identify the motivation among different athletics groups and see the influence motivational profile of satisfaction feel them. The sample was composed of 51 subjects from schools and sport clubs in Murcia. The sample was classificated according to gender, age, frequency of practice, possession of federal license and type training. As instruments were used three test; BREQ-2 for self-determination, TEOSQ, for motivacional orientation and SSI, for satisfaction level. All them, adapted to the context athletic.The results showed more satisfaction level and less bore level in subjects with high task orientation and intrinsic motivation/self-determined, and greater motivation to achieve (ego and task). The ideal profile were younger women, federated, which train them frequently and always accompanied. The age was the most influential factor. These results could be studied by the coaches in order to they keep in mind the variables that can be modified such as training methodology to achieve greater satisfaction and of this form, a better adherence and competitive results. It would be wise to consider athletes from an early stage was facing the enjoyment of athletics for the future, not to reduce their level of satisfaction and motivation, increasing the possibility of sport dropout.